First-year metabolic control guidelines and their impact on future metabolic control and neurocognitive functioning in children with PKU - de la Parra, Alicia (Mol Genet Metab Rep, 2017)
There is a consensus on the importance of early and life-long treatment for PKU patients. Still, differences exist on target blood phenylalanine (Phe) concentrations for children with PKU in different countries and treatment centers. For the first time, long-term metabolic control and child development and cognitive functioning is compared between children with mean phenylalanine concentrations under 240 μmol/L (group A), between 240 and 360 μmol/L (group B) or over 360 μmol/L (group C) during their first year of life. METHODS: 70 patients diagnosed with PKU through neonatal screening with Phe > 900 μmol/L, were divided into 3 groups: A, B and C, according to mean Phe concentrations and standard deviation (SD). Metabolic control during childhood, psychomotor development and IQ were compared. RESULTS: In group A, Phe was maintained within the recommended range until 6 years of age, in Group B, until 3 years of age, and in group C, Phe was always over the recommended range. No significant differences were found between the three groups in mental development index (MDI) and motor development index (PDI) scores at 12, 24, and 30 months of age, but group C had the lowest scores on MDI at all age periods. At preschool and school age, IQ was higher in group A compared to group C. CONCLUSION: Results show that mean blood Phe concentrations between 120 and 240 μmol/L during first year of life have a positive impact in metabolic control and cognitive functioning during childhood.